Procedimiento de cadena de custodia sobre contenido digital y su valoración como prueba documental dentro del Código Orgánico Integral Penal - León Cabrera, Javier Fernando León Cabrera (2015)
This thesis will address a topic of great importance that has been poorly developed and exploited in our Ecuadorian legal system. The chain of custody of digital content in the new Code Integral Criminal becomes fundamental to the development of legal research contribution, management and treatment should be considered high risk because of their fragility and constant tendency to alterations that may It is caused by various factors. Ecuador is part of the group of Latin American countries have legislation that regulates high tech crime and management of a chain of custody for digital content, sought to create confidence in this type of evidence admissible in generating legal proceedings. Comprehensive Organic Penal Code Article 500 defines its digital content as any computer act representing facts, information or concepts of reality, stored, processed or transmitted by any technological medium that lends itself to computer processing, including programs designed to an isolated, interconnected or interrelated technological equipment. The digital content presented as evidence must retain and demonstrate that its integrity has not been altered in any investigative stage, to become a different traditional test are predisposed to a modification to a doubling or a partial or total elimination of their contents creating disability and subsequent annulment of the trial within a trial. It is important to recognize that such may be the only evidence linking a suspect to a crime whether it is a technological or a conventional crime, for that reason deserves all the technical and legal care of the case.